EP486 Brain metastases from endometrial cancer: a case report. (1st November 2019) - Castro Oliveira, L; Rolo, AS; Freitas Lima, B; Carvalho, C; Faustino, I; Fardilha, C; Teixeira, A; Costa, P; Coutinho, C
Abstract : Introduction/Background: Endometrial carcinoma (EC) is the most common invasive gynaecologic neoplasm. Brain metastases from EC are rare and they confer a poor prognosis. Methodology: Clinical case report of a patient with brain metastases from EC. Results: A 62 year-old woman presented in April 2011 with vaginal bleeding. She was diagnosed with EC and she underwent a total hysterectomy with bilateral salpingo-oophorectomy. Histology showed an endometriod adenocarcinoma grade1, myometrial invasion <50%, without lymphovascular invasion; FIGO stage IA. In May 2013, she start with abdominal pain and swelling. The CT scan revealed ascites, peritoneal carcinomatosis and lymph nodes (LN) metastases and she completed six cycles of carboplatin AUC5 and paclitaxel 175 mg/m 2 until December 2013 with partial response. In June 2014, the patient presented with confusion and headache. Brain CT of the brain revealed diffuse brain metastases. She received steroids and whole-brain radiation therapy (WBRT) to a total dose of 30 Gy until July 2014. Thereafter, with no evidence of visceral or LN metastases, she received megestrol 160 mg daily between July and October 2014. In October 2014, peritoneal relapse was diagnosed and she received cisplatin 50 mg/m² and adriamycin 60 mg/m² between October 2014 and February 2015 with partial response. In June 2015, the patient presented headache with new brain lesions and she underwent WBRT to a total dose of 20 Gy until August 2015. In October 2015, peritoneal and LN relapse was diagnosed and she received topotecan 1 mg/m 2 days 1–5 21/21 days between October 2015 and October 2016. The patient died in November 2016, 29 months after brain spread. Conclusion: Patients with EC that present with neurologic signs and symptoms should be evaluated for brain metastases because early diagnosis and promptly multimodal treatment can improve the prognosis of these patients. Disclosure: Nothing to disclose.